Genetic polymorphisms of human platelet antigens-1 to -6, and -15 in the Malaysian population - Tan, J.Y.; Lian, L.H.; Nadarajan, V.S. (2012)
BACKGROUND: Human platelet antigens (HPA) are determinant in several platelet-specific alloimmune disorders, such as neonatal alloimmune thrombocytopenia, post-transfusion purpura and platelet transfusion refractoriness. The distribution of HPA systems in the Malaysian population is not known. Defining the patterns of HPA systems provides a basis for risk assessment and management of the above complications. MATERIALS AND METHODS: The aim of this study was to investigate the distribution of HPA -1 to -6 and -15 in the three major ethnic groups (Malay, Chinese and Indian) in the Malaysian population. A total of 600 random donor samples, 200 from each of the three ethnic groups, were genotyped by means of real time polymerase chain reaction (PCR) with hydrolysis probes and PCR-restriction fragment length polymorphism (PCR-RFLP). RESULTS: The most common genotype observed in this study was HPA-1a/1a-2a/2a-3a/3b-4a/4a-5a/5a-6a/6a-15a/15b (17%) followed by HPA-1a/1a-2a/2a-3a/3a-4a/4a-5a/5a-6a/6a-15a/15b (14.33%). The allele frequencies of HPA in Malays and Chinese were found to be similar those of other East and South-East Asian populations, while those of Indians were comparable to the frequencies found in Europeans. CONCLUSION: The results of this study have been useful for determining the distribution of HPA polymorphisms in this region and for potential clinical implications